Learning the skill of mixing spices - Mumbai Archive Project Team (Jio Institute, 2024)
Veera Almeida runs her business from home, making and sharing her recipes online through social media. The ingredients and preparation style are passed down through generations in the family, from mother to daughter to granddaughter. The skill of mixing spices is learned through years of apprenticeship in the kitchen rather than by relying on a cookbook.